Trisomy 8 (Warkany Syndrome 2) Report Of Two Cases - Talavera-Vargas-Machuca, Sergio (2016)
Trisomy 8 is an uncommon anomaly in neonates, frequently being a lethal condition among individuals with pure trisomiclines and more tolerable in mosaics cases. This aneuploidy is mainly characterized by a moderate - severe intellectual deficitand poor motor coordination. Affected individuals presents craniofacial malformations, prominent forehead, arched palate,deformed ears with low implantation, elongated trunk, reduced motility, articular defects and deep plantar grooves, which isone of the main characteristics of this condition. Abnormalities of internal organs are of varying severity. We present the reportof two cases of trisomy 8 or Warkany syndrome 2 born at Instituto Nacional Materno Perinatal.